IMPACT OF COVID-19 ON INCOME OF TRADERS FOOD MARKET KURAI TAJI KOTA PARIAMAN - Intan Sri Dewi (JURNAL BUANA, 2022)
Coronavirus is a virus similar to the common cold or the common cold that can cause mild to serious illness. Meanwhile, the virus that caused a stir in Indonesia, which originated from China, was the Corona Virus. The new corona virus was discovered to cause the coronavirus disease Covid-19. Covid-19 is an infectious disease and was only discovered when the outbreak started in Wuhan, China in December 2019. West Sumatra is one of the provinces with a relatively dense population. With 7 cities and 12 regencies. One of the cities in West Sumatra, namely Kota Pariaman, has felt the impact of Covid-19, Kota Pariaman is famous for the Balai Kurai Taji Market. The traders at the Balai Kurai Taji Market are currently screaming because of the rampant Covid-19 outbreak by reducing the income of traders, especially food traders. The influence that traders feel the most at the Balai Kurai Taji market is the implementation of the social distancing policy issued by the Indonesian Government. As a result, some traders are confused and their income is threatened with a severe deficit. Based on the results of the t-test calculation, it can be seen that the value of tcount = 7.25 > ttable ( = 0.05/20) = 1.69. This means that Ho is rejected and H1 is accepted, thus the hypothesis that there is an impact of covid 19 on the income of traders, meaning that the income of traders before covid 19 is greater than after covid 19.